Chrysin's dose-dependent effects on steroidogenesis in female BALB/c mice: In vivo study of adrenal, ovarian, and uterine hormone regulation - Khalid M. Alqaisi; Manal A. Abbas; Rand Alshawawreh (Pensoft Publishers, 2024)
Background: Chrysin is known for its pharmacological effects and structural resemblance to estrogen. The study explores the impact of chrysin on steroidogenesis focusing on adrenal and ovarian steroidogenic enzymes. Materials and methods: Thirty female BALB/c mice were divided into three groups: a control group and two chrysin-treated groups (50 mg and 100 mg). Gene expression of key steroidogenic enzymes was assessed in adrenal glands and ovaries using RT-qPCR. Uterine expression of estrogen receptor alpha (ERα) was also examined. Histological analysis of adrenal glands and ovaries was performed. Results: High-dose chrysin downregulated CYP17A1 expression in adrenal glands compared to control and low-dose groups. In contrast, 3β-HSD was significantly downregulated in the high-dose group. In ovaries, high dose chrysin reduced aromatase expression. Conclusion: Our findings revealed that chrysin's impact on steroidogenesis is dose-dependent. By downregulating CYP17A1 in adrenal glands, potentially affecting androgen and estrogen synthesis, and enhancing aromatase expression in ovaries at lower doses.